Coordination Chemistry Inside Polymeric Nanoreactors: Interparticle Metal Exchange and Ionic Compound Vectorization in Phosphine‐Functionalized Amphiphilic Polymer Latexes. Issue 18 (22nd March 2016) - Chen, Si; Gayet, Florence; Manoury, Eric; Joumaa, Ahmad; Lansalot, Muriel; D'Agosto, Franck; Poli, Rinaldo
Abstract: Stable latexes of hierarchically organized core‐cross‐linked polymer micelles that are functionalized at the core with triphenylphosphine (TPP@CCM) have been investigated by NMR spectroscopic analysis at both natural (ca. pH 5) and strongly basic (pH 13.6) pH values after core swelling with toluene. The core–shell interface structuring forces part of the hydrophilic poly(ethylene oxide) (PEO) chains to reside inside the hydrophobic core at both pH values. Loading the particle cores with [Rh(acac)(CO)2 ] (acac=acetylacetonate) at various Rh/P ratios yielded polymer‐supported [Rh(acac)(CO)(TPP)] (TPP=triphenylphosphine). The particle‐to‐particle rhodium migration is very fast at natural pH, but slows down dramatically at high pH, whereas the size distribution of the nanoreactors remains unchanged. The slow migration at pH 13.6 leads to the generation of polymer‐anchored [Rh(OH)(CO)(TPP)2 ], which is also generated immediately upon the addition of NaOH to the particles with a [Rh(acac)(CO)] loading of 50 %. Similarly, treatment of the same particles with NaCl yielded polymer‐anchored [RhCl(CO)(TPP)2 ]. Interparticle coupling occurs during these rapid processes. These experiments prove that the major contribution to metal migration is direct core–core contact. The slow migration at the high pH value, however, must result from a pathway that does not involve core–core contact. The facile penetration of the polymer cores by NaOH and NaCl results from the presence of shell‐linked poly(ethylene oxide) methyl ether functions both outside and inside the polymer core–shell interface. Abstract : Controlling migration : The molecular dynamics of core‐cross‐linked micelle (CCM) latexes is revealed by NMR spectroscopic studies of interparticle metal migration at different pH values (see figure; PEO=poly(ethylene oxide)). The peculiar interface structuring of these polymeric nanoreactors accounts for the rapid vectorization of ionic compounds from the aqueous phase to the hydrophobic core.